Study of improvement of indices maize line to establish their position in hybrids - Oxana DIRZU-COCOS (Eastern European Journal of Regional Studies, 2015)
Corn (Zea mays L.) crop that is grown on large areas - over 140 million hectares worldwide, and 400-500 thousand ha in Moldova due to production potential broad diversity of use as food for humans, animals, birds raw material for industrial processing. The upward trend in average yields achieved is largely attributed to the improvement of scientific programs. Select the line with the characters and traits that are transmitted hereditary hybrids and contribute to their performance, ensure progress in improvement. Therefore, the process of creating inbred lines associated with combining ability testing as a measure of productivity conferred hybrids, is significant research programs. Orientation purpose of improved maize hybrids to formulas and simple change to a superior capitalization heterosis effect and perfect uniformity of plant requires changes in methodology for the creation, evaluation and classification of inbred lines.